Back to the Real: Efficacy and Perception of a Modified Cognitive Interview in the Field. Issue 5 (6th August 2013) - Colomb, Cindy; Ginet, Magali; Wright, Daniel; Demarchi, Samuel; Sadler, Christophe
Summary Since the Cognitive Interview (CI) was developed, many experiments have been published, but only two have investigated its efficacy in real criminal cases. Here, a Modified CI (MCI) is tested with real interviews in an inquisitor justice system. Several moderators and the interviewers' attitudes towards the CI/MCI are also examined. Eighty‐one witnesses were interviewed by 27 French military police officers, with a Standard Police Interview, a Structured Interview (SI), or an MCI. The MCI produced the most forensically relevant information, especially for victims. Trainees judged the SI and the MCI useful, usable, and acceptable, and felt efficient in using them, beliefs that increased after 1 year of practice. The self‐efficacy was linked with the declared use of the techniques. In all, this study confirmed the efficacy of the CI/MCI as a tool to be used in the field, with some cautions to be underlined, notably because of the small sample size considered. Copyright © 2013 John Wiley & Sons, Ltd.